2007
DOI: 10.1123/jsr.16.1.2
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Tibial Rotation on the Presence of Instability in the Anterior Cruciate Ligament Deficient Knee

Abstract: Context:The effects of tibial rotation after ACL injury have not yet been well determined. Objective: To show whether clinical outcomes such as the amount of tibial rotation can affect functional outcomes in normal and ACL de! cient knees. Design: Case control study. Setting: Research laboratory. Participants: Twenty normal subjects (Control) and 20 subjects with ACL de! cient knees (ACL). Main Outcome Measures: Tibial rotation at 30 and 90 degrees of knee " exion was measured using an inclinometer. One-legged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 26 publications
2
9
0
Order By: Relevance
“…More than 18 degrees is defined as the external torsion, and less than 13 degrees is considered as internal torsion [33,34]. The present study was consistent with the reports of Samu Kawa et al [13] and indicated that futsal players with hamstring tightness had increased tibial torsion as compared to the control group. On the other hand, the later consisting of 20 normal subjects and 20 subjects with ACL-deficient knees, showed that the amount of tibial rotation was higher in ACL ruptured knees than in uninjured knees, and such higher amounts of tibial rotation affected the figure-ofeight running index.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…More than 18 degrees is defined as the external torsion, and less than 13 degrees is considered as internal torsion [33,34]. The present study was consistent with the reports of Samu Kawa et al [13] and indicated that futsal players with hamstring tightness had increased tibial torsion as compared to the control group. On the other hand, the later consisting of 20 normal subjects and 20 subjects with ACL-deficient knees, showed that the amount of tibial rotation was higher in ACL ruptured knees than in uninjured knees, and such higher amounts of tibial rotation affected the figure-ofeight running index.…”
Section: Discussionsupporting
confidence: 90%
“…For instance, Haim et al (2006) investigated the validity of clinical and radiological features of patellofemoral pain syndrome (PFPS) [12]. Samu Kawa et al (2007) also examined the effect of tibial rotation on the presence of instability in case of anterior cruciate ligament deficiency [13].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies that have used a clinical testing apparatus to look for side-to-side differences in the range of tibial rotation in the right and the left knees are nearly identical (Shoemaker & Markolf 1982;Lusin & Gajdosik, 1983;Samukawa et al, 2007). A significant side-to-side correlation was found in the present research.…”
Section: Discussionsupporting
confidence: 60%
“…They reported an increase in AP translation between 34% and 57% depending on the flexion angle. Similarly, Samukawa et al (2007) reported an increase in IE rotation between 29% and 39% in the ACL-deficient knees. These clinical findings support the results of the present study.…”
Section: Discussionmentioning
confidence: 92%